Analisis prospektif pengembangan agrotechnopreneurship berbasis potensi sektor pertanian di Kabupaten Jember [Prospective analysis of potential-based agrotechnopreneurship development in the agricultural sector in Jember Regency] - Wibowo, Yuli; Soekarno, Siswoyo; Wiyono, Andi Eko; Fajriyah, Ajeng Afriska Lailatul; Windiari, Eva Yulia (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2024)
The pandemic several years ago has impacted employment problems with the increase in the number of unemployed in Jember Regency. One effort can be made to develop agrotechnopreneurship as a community business. This study aims to analyze the prospects for developing agrotechnopreneurship by utilizing the potential of the agricultural sector in Jember Regency. The analysis focused on potential agrotechnopreneurship products developed in Jember Regency today: mocaf, chili sauce, coconut briquettes, shredded catfish, and cow's milk kefir. This research uses a prospective analysis method structured based on states that may occur in the future. The results showed several scenarios for developing potential agrotechnopreneurship in Jember Regency, generally including optimistic and pessimistic scenarios. The development of agrotechnopreneurship in chili sauce, coconut briquettes, shredded catfish, and cow's milk kefir has an optimistic scenario, indicating a promising potential for future growth. This optimistic scenario can be realized if the key factors in the development of agrotechnopreneurship can be improved as expected. Meanwhile, the development of mocaf agrotechnopreneurship has a pessimistic scenario. Keywords: agrotechnopreneurship, Jember Regency, prospective analysis, the agricultural sector